2012
DOI: 10.2306/scienceasia1513-1874.2012.38.095
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Large scale biodiesel production by using low cost and abundant feedstock as waste animal fat is becoming more important due to petroleum reserves crisis and adverse environmental problems. This paper has experimentally developed a new method for lard synthesis by using suitable conditions of production with high solvent blending. A polynomial equation was obtained for lard biodiesel yields as a function of synthesis parameters. The validity of the predictive model was confirmed by validation experiments. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Based on this theoretical view, it seems unsuitable to increase the overall solubility between methanol and oil with n -hexane as a co-solvent. However, authors have reported a yield increase by using n -hexane as the co-solvent in the range of 7 wt% up to 35 wt% [ [43] , [44] , [45] , [46] , [47] , [48] , 59 ].…”
Section: Co-solvents In Homogeneously Alkaline Catalysed Methanolysismentioning
confidence: 99%
“…Based on this theoretical view, it seems unsuitable to increase the overall solubility between methanol and oil with n -hexane as a co-solvent. However, authors have reported a yield increase by using n -hexane as the co-solvent in the range of 7 wt% up to 35 wt% [ [43] , [44] , [45] , [46] , [47] , [48] , 59 ].…”
Section: Co-solvents In Homogeneously Alkaline Catalysed Methanolysismentioning
confidence: 99%
“…Several researchers explored the possibility of pig fat as a feedstock for biodiesel production. Janchiv et al . obtained the waste pork lard from a local market.…”
Section: Biodiesel Synthesis From Fatty Wastesmentioning
confidence: 99%
“…Several researchers explored the possibility of pig fat as a feedstock for biodiesel production. Janchiv et al [81] obtained the waste pork lard from a local market. To identify the optimal conditions for maximum biodiesel production from pork lard, methanol to oil molar ratio was varied from 6:1 to 18:1 and catalyst concentration was varied from 0.48-3.05 wt%.…”
Section: Pig Fatty Wastementioning
confidence: 99%
“…Lard is a co‐product extracted from pig slaughter residues in meat‐packing industry or generated during cooking or roasting pork. Waste lard has already been used in biodiesel production alone 3–10 or mixed with vegetable oils 11, 12. In general, several methods of transesterification of TAGs into biodiesel from lard have been employed like homogeneously, heterogeneously and enzymatically catalyzed as well as noncatalyzed processes (Tab.…”
Section: Introductionmentioning
confidence: 99%
“…1). The conventional homogeneously catalyzed reactions can usually be performed in single 3–7, 11, 12 or two 8–10 steps, using methanol at the alcohol‐to‐fat molar ratio of 6:1 or higher, a catalyst amount of about 1 % (based on the fat weight), and a reaction temperature of 60 °C. Single‐step processes are acid‐ or base‐catalyzed, while two‐step processes consist of an acid‐catalyzed free fatty acid esterification, commonly considered as a pretreatment step, followed by a base‐catalyzed transesterification step.…”
Section: Introductionmentioning
confidence: 99%